OPTIMASI PENAMBAHAN KONSENTRASI UREA DALAM SUBSTRAT PADA PRODUKSI DAN SIFAT ORGANOLEPTIK NATA DARI AIR LEGEN - K. Ni'mah; Ngadiani Ngadiani (FMIPA : Universitas PGRI Adi Buana, 2013)
The aim of this study to find optimum concentration of urea in production, firmness and sensory properties of nata. This study was conducted using a completely randomized experimental design consisting 4 levels concentrations of urea (3, 4, 5 and 6 g/ l) with 6 replication. Fermentation processes were conducted using Acetobacter xylinum in room temperature (27oC) under light condition for 10 days. The results showed that the urea concentration in substrate medium significantly (P<0.05) effect on production and firmness nata. Highest production (503.5±72,5 g/l) and firmness (32.25±1.48 mm/s) of nata have obtained from 4 g/l urea in medium. Neverless, panelist most prepered color of nata from 6 g/l urea. Meanwhile panelists most prepared taste and smell of nata from 4 g/l. Key words: urea, water legen, Nata, Acetobacter xylinum, production, firmness, organoleptic